Improving the Activity of M−N4 Catalysts for the Oxygen Reduction Reaction by Electrolyte Adsorption. Issue 23 (7th November 2019) - Svane, Katrine L.; Reda, Mateusz; Vegge, Tejs; Hansen, Heine A.
Abstract: Metal and nitrogen codoped carbons (M−N/Cs) have emerged as promising alternatives to platinum‐based catalysts for the oxygen reduction reaction (ORR). DFT calculations are used to investigate the adsorption of anions and impurities from the electrolyte on the active site, modeled as an M−N4 motif embedded in a planar carbon sheet (M=Cr, Mn, Fe, Co). The two‐dimensional catalyst structure implies that each metal atom has two potential active sites, one on each side of the sheet. Adsorption of anions or impurities on both sites results in poisoning, but adsorption on one of the sites leads to a modified ORR activity on the remaining site. The calculated adsorption energies show that a number of species adsorb only on one of the two sites under realistic experimental conditions. Furthermore, a few of these adsorbates modify the adsorption energies of the ORR intermediates on the remaining site, in such a way that the limiting potential is improved. Abstract : Poisonous species : The adsorption of anions and impurities from the electrolyte on nonprecious M−N4 catalysts (M=Cr, Mn, Fe, Co) for the oxygen reduction reaction (ORR) is investigated through DFT calculations. Some combinations of metal and adsorbate lead to an improvement in the limiting potential for the ORR, and poisoning of catalysts by adsorption to active sites can be predicted.